DEVELOPMENT OF PROFESSIONAL CAREER PLANNING SKILLS IN FUTURE TEACHERS (TAMADDUN NURI JURNALI, 2024)
In this article, in the process of continuous education, the problems and characteristics of the future teacher in the professional development, special attention is paid to the stage of professional education, and the procedural content of the formation of the future teacher's career in the stage of professional activity. A variant of the model is offered.